Enterobactericeae Sebagai Bakteri Patogen Infeksi Nosokomial di Rumah Sakit - Putri, Abrila Tamara; Soleha, Tri Umiana; Nareswari, Shinta; Ramadhian, M. Ricky (CV. Jasa Sukses Abadi, 2024)
Enterobactericeae are gram-negative rod bacteria which are often pathogenic bacteria that cause nosocomial infections. Enterobactericeae bacteria have several characteristics including small size and rod shape, natural habitat in the digestive tract of humans or animals and some others originate from bodies or inanimate objects, are motile and non-motile, cannot form spores, and are aerobic to facultative anaerobic. Nosocomial infections are infections that are acquired during the health care process at the hospital, but are not present when the patient is admitted to the hospital. The source of transmission of nosocomial infections can result from direct or indirect contamination in the health care process in hospitals. Common nosocomial infections include Central Line Associated Blood Stream Infection (CLABSI), Catheter Associated Urinary Tract Infection (CAUTI), Surgical Site Infection (SSI), and nosocomial pneumonia consisting of Hospital Acquired Pneumoniae (HAP), Ventilator Associated Pneumoniae (VAP), and Health Care Associated Pneumoniae (HCAP). The Enterobactericeae bacteria that often cause nosocomial infections in hospitals include Escherichia coli, Klebsiella sp, Enterobacter sp, Pseudomonas sp, and so on. Nosocomial infections have a negative impact on the health recovery process of inpatients in hospital, so they need to be handled well and preventive efforts are made to avoid this undesirable event through health service efforts that comply with standard operational procedures and pay attention to aseptic principles.